Стертая: [роман : для старшего школьного возраста] / Тери Терри - Терри Тери (Young Adult, 2019)
Экземпляры: ЦБ (20191111) / Инвентарный номер: 94589 / Цена: / Сис.шифр: 84(4=432.1)-44 / Авт.знак: Т 35 / ББК: 84(4=432.1)-44